Understanding the growth of the middle class in Bolivia - Javier Beverinotti; Gustavo Canavire-Bacarreza; Alejandro Puerta (Inter-American Development Bank (IDB), 2021)
In this paper we aim to disentangle how sectoral economic growth affects the size of the middle class, using state-level data of Bolivia from 2000 to 2017 and breaking the three main economic activities into subsectors to attain more-specific results. Because the data from Bolivia are limited, we utilize a Bayesian hierarchical longitudinal model for small samples. We find that the commerce and services sectors have the biggest impact on the size of the middle class in Bolivia and that mining and agriculture have a similar though smaller effect. Our results also suggest that both formality and public social investment do have significant effects, albeit smaller ones.
Keywords: C23; D63; I32; O41; 330; middle class; economic growth; informality